Motivations in volunteer work - Ferreira, Marisa R. (2009)
The objective of this paper is to review and discuss the literature about volunteers’ motivations to donate their time to NGOs (Non Governmental Organisations). According to Parboteeah, Cullenb & Lim (2004) management research has not paid much attention to voluntarism, however, voluntarism is a substantial part of productive work for many societies. Wilson & Pimm (1996) show that in Great Britain about 39% of the adult population has been involved in some volunteer activity for some period of time. In the U.S.A. these values reach 50% (Wilson & Pimm, 1996). Considering the benefits that voluntarism can bring to an organisation, we understand that more attention must be devoted to this phenomenon. The more an organisation knows volunteers, the better this organisation will be able to meet the needs and expectations of these individuals. We present a literature review that illustrates and compares the different motivations associated with volunteer work. The paper includes a bibliographical databases search in specialised journals. The search used the key words “motivations” and “voluntarism” (in the heading and text body) and covered all numbers between 2000 and 2007. We identify the existence of repeated motivations (Holmberg & Söderlung, 2005; Prouteau & Wolff, 2008; Soupourmas & Ironmonger, 2001; Yavas & Riecken, 1997), which allow the establishment of a typology of volunteers’ motivations, based on four categories: altruism, social needs, self-esteem, learning and self-development. Finally we identify three main gaps in the literature that justify further research. First, research focusing on the differences between motivations related to volunteers’ "Attraction" versus "Retention" in NGO’s is nil. Second, the great majority of the studies rely on north American (USA and Canada) and Australian context, which demands for further research in European countries. Third, the majority of NGOs researched are related to sport, art or the environment, and it would be interesting to explore the relationship between motivation and NGO type. These questions may obtain interesting answers for NGO management, in particular with regard to volunteer attraction and retention.